?-Secretase BACE1 regulates hippocampal and reconstituted M-currents in a ?-subunit-like fashion - Heßler, Sabine; Zheng, Fang; Hartmann, Stephanie; Rittger, Andrea; Lehnert, Sandra; Voelkel, Meike; Nissen, Matthias; Edelmann, Elke; Saftig, Paul; Schwake, Michael; Huth, Tobias; Alzheimer, Christian (The Journal of Neuroscience, 2015)
The ?-secretase BACE1 is widely known for its pivotal role in the amyloidogenic pathway leading to Alzheimer's disease, but how its action on transmembrane proteins other than the amyloid precursor protein affects the nervous system is only beginning to be understood. We report here that BACE1 regulates neuronal excitability through an unorthodox, nonenzymatic interaction with members of the KCNQ (Kv7) family that give rise to the M-current, a noninactivating potassium current with slow kinetics. In hippocampal neurons from BACE1(-/-) mice, loss of M-current enhanced neuronal excitability. We relate the diminished M-current to the previously reported epileptic phenotype of BACE1-deficient mice. In HEK293T cells, BACE1 amplified reconstituted M-currents, altered their voltage dependence, accelerated activation, and slowed deactivation. Biochemical evidence strongly suggested that BACE1 physically associates with channel proteins in a ?-subunit-like fashion. Our results establish BACE1 as a physiologically essential constituent of regular M-current function and elucidate a striking new feature of how BACE1 impacts on neuronal activity in the intact and diseased brain.
EVALuna2:2474